2009
DOI: 10.1002/jcop.20335
|View full text |Cite
|
Sign up to set email alerts
|

Escaping homelessness: anticipated and perceived facilitators

Abstract: One study with two distinct sections was conducted to identify factors facilitating escape from homelessness. In Section 1, 58 homeless individuals rated possible facilitators of escape (factors they believed would help them become more independent and self-sufficient). In Section 2, 80 participants who had already exited homelessness rated the same facilitators (factors that would have helped them become more independent and self-sufficient) and the importance of actual factors that facilitated escape. When r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…However, a smaller yet growing portion of research into homelessness has moved toward identifying the psychological strengths necessary for well-being despite homelessness (Tweed et al 2012;Kidd and Davidson 2007;BiswasDiener and Diener 2006;Kosor and Kendall-Wilson 2002). In fact, psychological strengths are also important to overcoming homelessness, as found in a study by Patterson and Tweed (2009) of formerly homeless individuals that suggests psychological strengths can fuel the resilience necessary to overcome barriers, such as poverty, that perpetuate homelessness. An additional study of individuals who were formerly homeless also supports that psychological strengths help to generate the determination needed to escape homelessness (MacKnee and Mervyn 2002).…”
Section: Implications In the Context Of Homelessnessmentioning
confidence: 99%
“…However, a smaller yet growing portion of research into homelessness has moved toward identifying the psychological strengths necessary for well-being despite homelessness (Tweed et al 2012;Kidd and Davidson 2007;BiswasDiener and Diener 2006;Kosor and Kendall-Wilson 2002). In fact, psychological strengths are also important to overcoming homelessness, as found in a study by Patterson and Tweed (2009) of formerly homeless individuals that suggests psychological strengths can fuel the resilience necessary to overcome barriers, such as poverty, that perpetuate homelessness. An additional study of individuals who were formerly homeless also supports that psychological strengths help to generate the determination needed to escape homelessness (MacKnee and Mervyn 2002).…”
Section: Implications In the Context Of Homelessnessmentioning
confidence: 99%
“…Further, as stated earlier, Shneidman (1999) suggested that psychache is caused by unfulfilled needs which, if unmet, may lead to psychache. Research findings are that homeless people feel socially outcast, alone, and inferior (Patterson & Tweed, 2009). Given that people who are homeless likely have various unfulfilled needs (although no research currently exists), psychache is thus expected to be especially prevalent among homeless individuals.…”
Section: Application To People Who Are Homelessmentioning
confidence: 99%
“…Patterson and Tweed (2009) noted that while a large body of evidence supports the relationship between social support and well‐being, there is evidence that those struggling with poverty have little if any support mechanisms and may not perceive them in the same ways as non‐impoverished individuals. In a study with homeless individuals, for example, they asked participants to rate the level to which support was needed to move out of homelessness.…”
Section: Empirical Referentsmentioning
confidence: 99%